Selected writings on financial and economical behaviours in the new economy - Pelenk, Saadet Ela (Cambridge Scholars Publishing, 2019)
The book evaluates the premise and consequences of financial behaviour in the new economy. It provides information about the financial and innovative behaviours of consumers in the new economy, where changing technology and knowledge are the main tools. It consists of two sections and nine chapters based on the financial behaviours of consumers and businesses in the new economy and the innovative approaches used in the employment, entrepreneurship and production processes. Today, both the consumers and the market-oriented enterprises are subject to financial contraction and expansion. Consumers.